2012
DOI: 10.4172/2161-069x.s8-001
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Inflammation and Lineage on Exfoliated Colonic Cells In Pediatric Inflammatory Bowel Disease

Abstract: Objectives The diagnosis (endoscopy, and biopsy) and continued clinical management of Inflammatory Bowel Disease (IBD), remain highly invasive, expensive, and inconvenient for the pediatric patient. The objective of this study was to see if colonocytes obtained from stools of subjects with IBD and normal controls would demonstrate higher levels of inflammatory markers (Cox 2 in CD45+ and CD45− cells) and if the inflammatory process and treatment effects would be reflected in an altered cytokine expression in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…4G). COX-2 is recognized as a reliable marker of colonic mucosal inflammation, and its expression has been shown to be markedly higher in IBD patients compared to healthy controls (31). Additionally, multiple studies have demonstrated that the IL-1 signaling pathway is involved in COX-2 up-regulation (32)(33)(34).…”
Section: Blockade Of Il-1α Has No Detectable Antiinflammatory Effect In Gfmentioning
confidence: 99%
“…4G). COX-2 is recognized as a reliable marker of colonic mucosal inflammation, and its expression has been shown to be markedly higher in IBD patients compared to healthy controls (31). Additionally, multiple studies have demonstrated that the IL-1 signaling pathway is involved in COX-2 up-regulation (32)(33)(34).…”
Section: Blockade Of Il-1α Has No Detectable Antiinflammatory Effect In Gfmentioning
confidence: 99%
“…Popivanova et al (2008) reported that the combined treatment with Azoxymethane and DSS induced the intracolonic expression of TNF-a and blocking of TNF-a reversed carcinoma progression with less inflammatory infiltrate. Cyclooxygenase-2 (COX-2), an inducible enzyme, drives inflammation and has been found to be highly expressed in patients with IBD (Nair et al, 2011). Interleukin-10 (IL-10), a potent anti-inflammatory cytokine, is capable of suppressing a number of proinflammatory signals associated with intestinal inflammatory diseases, such as ulcerative colitis and Crohn's disease (Fay et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Another study also reported the use of this noninvasive technique to isolate viable colonocytes from stools in IBD individuals and normal controls and showed altered levels of inflammatory markers and cytokine expression in the IBD individuals compared to controls. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%